THE MESSAGE OF DAKWAH IN THE CULTURE OF IMPLEMENTATION OF AKIKAH IN LEPPANGANG, PINRANG REGENCY (SEMIOTICS ANALYSIS) - Sulaiman, Sulaiha (IAIN Parepare, 2021)
This thesis discusses about cultural da'wah messages in the implementation of akikah in Leppangang, Pinrang Regency which combines sharia and culture by using semiotic analysis. This study aims to reveal the meaning of denotation and connotation in the implementation of akikah in Leppangang, Pinrang Regency. As well as knowing the meaning of cultural da'wah messages in the implementation of akikah in Leppangang, Pinrang Regency. This research is a qualitative research using a cultural da'wah review with semiotic analysis. The research approach used is more emphasis on theological and phenomenological. The sources of data for this research are traditional leaders, community, religious leaders, and the government. Data collection methods used in this study were observation, interviews, and documentation. The data processing technique used is the inductive method. The results of this study are reveal the meaning of denotation and connotation. So that in every tradition of carrying out aqikah in Leppangang, a concept is born of an embodiment or appearance of a sacred tradition and mythical thoughts emerge about what is believed and ultimately do not match what has been thought so far. In addition, it classifies three processes, namely: 1) The implementation of aqikah according to Islamic law, including: slaughtering aqikah animals, shaving the baby's hair, and giving names that contain da'wah messages in the form of worship, shari'a and morals 2) The process of Islamization in the implementation of akikah, includes: Reading barzanji ,Massorong reinforcements, and dio ute blood, 3) Traditions in the implementation of aqikah, include: serving reinforcements, carrying babies around the house, eating offerings, and mappenre tojang. The two processes that do not include the implementation of aqikah according to Islamic law contain a cultural meaning, namely the meaning of tafa'ul which is a prayer and good hope for the life of the child from the implementation of akikah.